2010
DOI: 10.1002/hfm.20237
|View full text |Cite
|
Sign up to set email alerts
|

Malaysian sitting anthropometry for seat fit parameters

Abstract: This article presents sitting anthropometry data for Malaysians focusing on seat fit parameters. It offers additional data regarding seat design requirements as there have been only a few efforts made to establish anthropometry data in Malaysia. An analysis using a measurement composed of 16 common and important dimensions in seat design was done with 216 subjects. Data collection was done by using direct measuring methods with standard equipment. Malaysian automobile seat fit parameters, namely backrest width… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Zakaria (2011) determined a sizing system for school uniforms. Daruis (2011) and Deros et al (2009) focused on improving chairs and seats for the Malaysian population, and the findings showed that the sitting dimensions of Malaysians are larger than the 95th percentile of other Asians. However, the sitting dimensions of Malaysians are smaller than those for Filipinos and Thais.…”
Section: Introductionmentioning
confidence: 95%
“…Zakaria (2011) determined a sizing system for school uniforms. Daruis (2011) and Deros et al (2009) focused on improving chairs and seats for the Malaysian population, and the findings showed that the sitting dimensions of Malaysians are larger than the 95th percentile of other Asians. However, the sitting dimensions of Malaysians are smaller than those for Filipinos and Thais.…”
Section: Introductionmentioning
confidence: 95%
“…In the evaluation of seats, different methods have been used to measure sitting comfort, such as anthropometry, subjective assessment, and objective measurements. In general, questionnaires are often developed to assess the comfort/discomfort levels for comparison purposes [ 23 , 24 , 25 ], whereas the anthropometric and biomechanical evaluations are used for chair designs [ 26 , 27 , 28 ] and load estimated on body regions [ 29 , 30 ], respectively. Body joint angle recoding is one of the methods for connecting the sitting posture and the comfort.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have stated the differences in anthropometric data between ethnic groups, and there may also be differences in a population [19][20][21]. Differences in parameter values for driver seats also occur between Malaysia's anthropometric data from the previous study [16,[19][20][21][22][23]. However, this study only involves the elderly who are older than 60 years and above, and the total number of study respondents involved for anthropometric measurement is only 56 respondents obtained from secondary data [14].…”
Section: Discussionmentioning
confidence: 95%